Shaped femtosecond laser induced photoreduction for highly controllable Au nanoparticles based on localized field enhancement and their SERS applications - Li Chen; Hu Jie; Jiang Lan; Xu Chenyang; Li Xiaowei; Gao Yunfeng; Qu Liangti (Nanophotonics, 2020)
Gold nanoparticles (Au NPs) have a wide range of applications because of their localized surface plasmon resonance properties. Femtosecond laser is considered to be an effective method for preparing Au NPs because of its characteristics of ultrashort irradiation periods and ultrahigh intensities. In this study, a novel method is proposed to produce an Au NP-attached substrate using the spatially and temporally shaped femtosecond laser. Laser-induced periodic surface structures (LIPSS) are designed to obtain the localized optical field enhancement, which leads to the femtosecond laser spatially reshaping, enabling the deposition of Au NPs by photoreduction on silicon substrates. The Au NPs prepared by this method exhibit morphological controllability and chemical stability, especially excellent spatial selectivity and uniformity, resulting in the tunable and stable surface-enhanced Raman scattering (SERS) applications. Also, the temporally shaped femtosecond pulses are introduced to further increase the enhancement factors of the SERS. This method successfully achieves the controllable morphology synthesis and selective deposition of Au NPs on the substrate simultaneously, which provides a promising candidate for SERS substrates fabrication, and holds potential applications in optoelectronics, such as molecular detection and biosensors.